Analisis Penggunaan Aplikasi Simba Dalam Pengelolaan Zakat Di Badan Amil Zakat Kota Bukittinggi - Nur Halimah; Aminah Nuriyah (Indonesian Journal of Islamic Economics and Business, 2023)
This thesis aims to discuss the use of the SIMBA application and discuss the level of effectiveness of SIMBA in the management of zakat funds at BAZNAS Bukittinggi. This research was conducted at the National Amil Zakat Agency (BAZNAS) of Bukittinggi City in 2022 using a qualitative approach where data collection was carried out by conducting interviews and document reviews. This study uses primary and secondary data obtained from BAZNAS Bukittinggi City. Researchers used data analysis to measure the level of effectiveness. In this study, it was found that SIMBA has been implemented by BAZNAS Bukittinggi City since 2018. The presence of SIMBA not only collects and records all existing data and activities, but also presents financial reports of all zakat fund management activities transparently and presented in balance sheets and other reports. The use of the SIMBA application has been proven effective with the achievement of indicators of effectiveness, namely the achievement of goals, integrity, and adaptation. In the results of the calculation and measurement of the effectiveness/efficiency ratio using the formula 19 the ratio of collection costs in 2021 with a result of 2.49% and formula 20 the ratio of collection in 2021 with a result of 0.28%. From the calculation results, it can be said that the collection of funds at BAZNAS Bukittinggi has been effective/efficient. The more effective/efficient the institution is in conducting collections, the better the governance of zakat institutions will be. Keywords: Management system, SIMBA, Zakat, effectiveness.